Audit Keamanan Sistem Informasi Berdasarkan Standar Iso 27001 Pada PT. BPR JATIM - Ermana, Fine; Tanuwijaya, Haryanto; Mastan, Ignatius Adrian (Jurnal JSIKA, 2012)
Information security management is extremely important for the head office of PT. BPR JATIM, since all report originating from branch offices throughout East Java will be sent to the center every day and network security in data transmission allows the risk of loss of confidential company data. Core Banking System operates online using the server at the vendor. However the central office still get regular reports from the branches that still have to have a data server backup and recovery. Given the importance of information, the information security police should include procedures for asset management, human resources management, physical and environmental security, logical security, operational security and information technology in information security incident handling. To find out how security information is in progress at the company, the need for security audit information system at PT. BPR JATIM to ensure that information security is implemented in accordance with the procedure. The standards used are ISO 27001 is selected because is very flexible depending on the needs of the organization developed and focused on information security management system.The result of the audit of the maturity level of the overall value of 2,90 which means that security controls are located on level 2 planned and tracked, but has approached the level 3 well defined which is the level expected by company, necessitating increased security controls that have been recommended.Keywords: audit, information security, ISO 27001, maturity level.